Critical review on battery thermal management and role of nanomaterial in heat transfer enhancement for electrical vehicle application. (December 2020) - Kumar, Pradeep; Chaudhary, Deepak; Varshney, Peeyush; Varshney, Utkarsh; Yahya, Syed Mohd; Rafat, Yasser
Highlights: Analysis of different types of available batteries. Different heat generation equations analysis. Analysis and comparison of different cooling strategies for thermal management. Effectiveness of nanofluids as thermal management strategy for lithium ion batteries. Abstract: The major issue with Lithium-ion batteries is their sensitivity to temperature. Lithium-ion cells do not perform efficiently at extreme temperature and adverse operating conditions, which can lead to thermal runaway of the battery pack. Lithium-ion batteries need to be thermally controlled within their working temperature range for their long-term durability and vehicle performance. This paper provides a review of different types of cooling strategies used in thermal management of the battery pack. Air-based, liquid-based, and Phase Change Material (PCM) based cooling methods are reviewed in this paper. Different types of battery pack arrangements as well as various heat generation methods are also reviewed. This study also presents a review of the use of nanomaterials to reduce the thermal issues of the battery pack. This paper highlights the use of nanomaterial to enhance the thermal conductivity of coolant (Phase Change Material as well as liquid coolant) used to bring the temperature of batteries in its optimum working range.